Effect of patchouli alcohol on the regulation of heat shock-induced oxidative stress in IEC-6 cells. (3rd July 2016) - Liu, Xiaoxi; Jiang, Linshu; Liu, Fenghua; Chen, Yuping; Xu, Lei; Li, Deyin; Ma, Yunfei; Li, Huanrong; Xu, Jianqin
Abstract: Purpose Patchouli alcohol (PA) is used to treat gastrointestinal dysfunction. The purpose of this study was to ascertain the function of PA in the regulated process of oxidative stress in rat intestinal epithelial cells (IEC-6).Materials and methods Oxidative stress was stimulated by exposing IEC-6 cells to heat shock (42 °C for 3 h). IEC-6 cells in treatment groups were pretreated with various concentrations of PA (10, 40, and 80 ng/mL) for 3 h before heat shock.Results Heat shock caused damage to the morphology of IEC-6 cells, and increased reactive oxygen species (ROS) level and malondialdehyde (MDA) content. Moreover, mRNA and protein expression by target genes related to oxidative stress in heat shock were also altered. Specifically, the mRNA expression by HSP70, HSP90, GSH-px, NRF2 nd HO-1 were all increased, and Nrf2 and Keap1 protein expression were increased after heat shock. However, pretreatment with PA weakened the level of damage to the cellular morphology, and decreased the MDA content caused by heat shock, indicating PA had cytoprotective activities. Pretreatment with PA at high dose significantly increased generation of intracellular ROS. Compared with the heat shock group alone, PA pretreatment significantly decreased the mRNA expression by HSP70, HSP90, SOD, CAT, GSH-px, KEAP1 and HO-1 . Furthermore, the high dose of PA significantly increased Nrf2 protein expression, while both the intermediate and high dose of PA significantly increased HO-1 protein expression.Conclusion Heat-shock-induced oxidative stress in IEC-6 cells, and PA could alleviate the Nrf2-Keap1 cellular oxidative stress responses.